A Typology of the Employment-Education-Location Challenges Facing Rural Island Youth - Gordon B. Cooke; Bui K. Petersen (Island Studies Journal, 2019)
We present a typology of ‘Stayers’ and ‘Leavers’ among rural island youth (aged 18-30) to illustrate their employment-education-location decision, based on semi-structured interviews with 30 young adults, and 81 older adults, in rural locations in Ireland, Newfoundland, Faroe Islands, and Shetland. Although there are exceptions, rural labour markets tend to be less diverse, and jobs in the primary sector, which have historically sustained these communities, face restructuring and decline in many places. Regardless of location, young people typically struggle to find good-quality work because of their relative lack of credentials and/or experience, and a shortage of local options can trap some, and force others to look ‘away’. Outmigration decisions are based on economics, but also social and emotional factors. Thus, even in places with low unemployment, young adults must consider where to live, and what to do next, and down the road. The reviewed literature suggests that there are commonalities among the choices typically facing those in rural and remote communities, whether on an island or on a mainland. We believe, though, that this dilemma can be exacerbated for those living on islands because of the logistical and psychological complexity of the ‘stay or leave’ decision. Rather than presenting detailed summaries from the young islanders whom we interviewed, our intended contribution is to present our typology as a way to spur on research towards specific policy remedies. The challenges facing any young rural islander can be complicated and individualized. Nonetheless, after conducting dozens of interviews in many island communities, some clear patterns of Stayers and Leavers emerged across the various jurisdictions. In turn, we argue for the development of social and economic policies tailored to suit each category of rural island youth.